High Sensitivity Detection of Activated Factor IX: Application to the Analysis of Different Therapeutical Factor IX Concentrates and Prothrombin Complexes - Kusch, Manuela; Seitz, Rainer; König, Herbert (Thrombosis and Haemostasis, 1998)
A very sensitive and highly reliable test system for the detection of activated coagulation factor IX (FIXa) has been established. This assay system is based on the cleavage of a fluorogenic substrate by activated factor X (FXa) which is generated by FIXa. This assay can be used to process a large number of samples at a time and, being based on the convenient microtiter plate format, can easily be adapted to automated processing for routine screening of large sample numbers.With this assay at hand we determined the FIXa content of different commercially available therapeutic FIX sources, such as high purity FIX (HPFIX) and prothrombin complex concentrates (PCC). Here we demonstrate that PCC from several suppliers do not contain significantly higher levels of FIXa as compared to HPFIX from the same supplier. In fact, there is a tendency for HPFIX to contain more FIXa than PCC. Moreover, HPFIX from certain manufacturers who do not produce PCC are characterized by an exceptionally high content of FIXa. Therefore, the higher thrombogenic potential of PCC which is well documented clinically cannot be explained solely – if at all – by an increased content of FIXa. Rather, it will be necessary to identify other components responsible for this phenomenon.